Pengaruh Sustainability Reporting, Green Accounting, dan Kinerja Keuangan terhadap Nilai Perusahaan - Zidan Naufal Akbar; Endah Susilowati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to test and analyze the effect of sustainability reporting, green accounting, and financial performance on firm value. The population used is all basic material sector companies listed on the Indonesia Stock Exchange for the period 2021-2023, with a total sample of 10 companies. The test method uses partial least square (PLS) which is processed with SmartPLS Version 3.0. The results showed that economic aspects in sustainability reports and financial performance affect firm value, while environmental aspects, social aspects, and green accounting have no effect on firm value.